Can Unstable Shoe Be Used As a Safety Training Shoe for Rehabilitation Exercises? - Amin Gandomkar; Mansour Eslami; Seyed Esmaeil Hosseini-Nejad; Vahid Jahedi (University of Social Welfare and Rehabilitation Sciences, 2014)
Objective: Unstable shoes have been recommended to osteoarthritis patients in order to reduce walking injuries. The aim of this study was to test the effect of unstable shoe on biomechanical selected variables related to injury during stanse phase of running. Materials & Methods: Twenty five healthy young male students available men (21±2.27years) participated in this study. Subjects were asked to ran on the force plate in barefoot, with unstable and control shoe conditions. Active and passive joint power, peak anterior-posterior forces, active and passive vertical force, loading rate and impulse of posterior and passive vertical forces variables were recorded using synchronizing force plate and video camera and calculated in MATLAB software. A repeated measure of ANOVA used to test the hypothesis in SPSS software (version 20, p<0.05). Results: negative power at Ankle joint decreased significantly by 49%, 35% using unstable shoe compared to contol shoe and barefoot conditions respectively (P=0.02,P<0.05). Furthemore, unstable shoe decreased significantly the active ankle power compared to barefoot condition by 23% (P=0.01). Loading rate and peak of passive vertical force, impulse and peak of posterior force increased significantly in unstable shoe compared to control shoe (P<0.05). Conclusion: Unstable shoe increased some of running related injuries risk factors such as Loading rate and peak of passive vertical force, impulse and peak of posterior force. Furthemore, this shoe could decrease absorption potential shank muscles and ankle active stability compared to control shoe. However, with increase of ankle active power compared to barefoot and lower anterior force, Unstable shoe could improve the ankle joint force generation and propulsion potential.